Organocatalytic asymmetric Michael/acyl transfer reaction between α-nitroketones and 4-arylidenepyrrolidine-2,3-diones - Parida, Chandrakanta; Pan, Subhas Chandra (Beilstein Journal of Organic Chemistry, 2021)
An organocatalytic asymmetric Michael/acyl transfer reaction between α-nitroketones and 4-arylidenepyrrolidine-2,3-diones is reported. A bifunctional thiourea catalyst was found to be effective for this reaction. With 10 mol % of the catalyst, good results were attained for a variety of 1,5-dihydro-2H-pyrrol-2-ones under mild reaction conditions.
Keywords: acyl transfer; enantioselectivity; Michael reaction; organocatalysis; pyrrolidine-2,3-dione